Folklore culturemes in the structure of cultural representations of Tuvan people - Moskvitcheva, Svetlana A.; Aleksandrova, Oksana I.; Ebzeeva, Yulia N. (The New Research of Tuva, 2022)
This article discusses the role and place of folklore in the system of cultural values of contemporary Tuvan society. The authors proceeded from the understanding of culture as a code, as a tool and as an imaginary space. The latter is associated with the concept of cultural representations that are present in the everyday, unreflected consciousness of culture bearers and represent their points of view on the culture itself. Unlike cultural declarations, representations are social in nature, not directly observable, but can be reached through analyzing epicultural discourses. Cultural representations play a threefold role in society: they provide meaning to a fragment of reality, integrate new meanings into already familiar knowledge systems, and make possible an exchange of meanings in society by maintaining its unity (S. Moscovici). While representations are static in nature and, according to our research, form a field-type structure, the dynamic components of social reality are attitudes associated with the activities and actions of members of a cultural society. In theoretical terms, our work is based on the distinction between two dimensions - the individual, i.e. memory and the cultural imaginary, and the social, to which history and cultural ideologies belong. The empirical part of the study includes a series of 30 research mini-interviews with young people from Tuva aged 17 to 27. Another part of it was a questionnaire filled in by 190 people aged 17 to 77. The questionnaire was compiled in line with the methodology of B. Morer and aimed to shed light on the structure of social representations of Tuvan culture and the place occupied by folklore in it. Representations of culture were evaluated by three indexed parameters — assessment, consensus and dispersion. Matching all of the three together allowed us to draft the central and the peripheral zones of culture, to pinpoint the prototypical culturemes, to assess the social consensus about the relative importance of any of the culturemes, and to forecast the sociocultural dynamics of the society. Our study has shown that the relationship between the “centre” and the “periphery” of culture is not hierarchical, since the normativity is determined by the centre, while the peripheral culturemes make the system more plastic.